If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -8x = 7x + -10x + -29 Reorder the terms: 6 + -8x = -29 + 7x + -10x Combine like terms: 7x + -10x = -3x 6 + -8x = -29 + -3x Solving 6 + -8x = -29 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -8x + 3x = -29 + -3x + 3x Combine like terms: -8x + 3x = -5x 6 + -5x = -29 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + -5x = -29 + 0 6 + -5x = -29 Add '-6' to each side of the equation. 6 + -6 + -5x = -29 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = -29 + -6 -5x = -29 + -6 Combine like terms: -29 + -6 = -35 -5x = -35 Divide each side by '-5'. x = 7 Simplifying x = 7
| 3x-2(7)=x | | 4(1+c)=3(c-4) | | .592n+60=5n-12-n | | 8(4c-1)-18=30c+8 | | w^2+19w+18= | | 6(y-2)=4y-22 | | w^2-w-30= | | (6x+3y+1)-(5x+2y-3)= | | w^2+13w-30= | | -16t^2+80t-96=0 | | y=0.2189x+15.61 | | x-50=.80(x-100) | | 5(4x-3)=21x | | 4x=49+3 | | (5a+3)+(7a+5)= | | -6m+7-6m+12=3m-5m+5-8m+2 | | 4(3c-1)-5=10c+9 | | .80(x-100)=450 | | -8(t+1)=0 | | 5(x-6)+8=7(x+2)-2 | | 6-2x=5x-9x+9 | | 9y+7=8y-5 | | 2(7+x)=11 | | -12-12-4x=32-28 | | 18x= | | 5(4z-1)-4(z+2)=14(z+1) | | -5z-13z+10=10+7z+3 | | x(3+x)+20=X^2-(x-5) | | 6k-2s=7-2k | | x^2+10x+25-y^2=0 | | 3(d-8)-5=9(d+2)-1 | | A*4-60=A |